2018
DOI: 10.1016/j.jacc.2017.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Adventitial and Perivascular Adipose Tissue Inflammation in Patients With Vasospastic Angina

Abstract: These results provide the first evidence that coronary spasm is associated with inflammation of coronary adventitia and PVAT, where F-FDG PET/CT could be useful for disease activity assessment. (Morphological and Functional Change of Coronary Perivascular Adipose Tissue in Vasospastic Angina [ADIPO-VSA Trial]; UMIN000016675).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 33 publications
2
90
0
2
Order By: Relevance
“…Recently, Ohyama et al demonstrated that the coronary perivascular TBR of adipose tissue was significantly increased in patients with vasospastic angina, as compared to controls (1.04 ± 0.03 vs. 0.85 ± 0.04, P b 0.01), and it was markedly decreased after long-term treatment with calcium-channel blockers [24]. These findings indicate that FDG PET/ CT could be useful for assessing disease activity even in low-grade inflammatory diseases.…”
Section: Follow-up Studiesmentioning
confidence: 98%
“…Recently, Ohyama et al demonstrated that the coronary perivascular TBR of adipose tissue was significantly increased in patients with vasospastic angina, as compared to controls (1.04 ± 0.03 vs. 0.85 ± 0.04, P b 0.01), and it was markedly decreased after long-term treatment with calcium-channel blockers [24]. These findings indicate that FDG PET/ CT could be useful for assessing disease activity even in low-grade inflammatory diseases.…”
Section: Follow-up Studiesmentioning
confidence: 98%
“…Recent study arguing perivascular fat has a role in spasm also support the atherosclerosis could influence the spasm by VSM contraction pathway 15 . But we consider more important factors for spasm is intra-lumen plaque which could more directly affect the luminal circumstances as resulting in flow limitation and obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…Исследования на животных продемонстрировали, что имплантация стента с лекарственным покрытием может усиливать воспаление адвентиции КА и вызывать их констрикцию посредством активации ROCK [30]. Доказано, что при ВС эпи-кардиальная и периваскулярная жировая ткань также вовлечены в патогенез неспецифического воспаления [31]. Дисфункция вегетативной нервной системы с преобладанием симпатических влияний в ночные часы может являться одной из причин многососудистого СКА.…”
Section: фр и патофизиологические детерминанты всunclassified